2012
DOI: 10.1128/jvi.06765-11
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the F-Protein Cleavage Site of Avian Paramyxovirus Type 7 Results in Furin Cleavage, Fusion Promotion, and Increased Replication In Vitro but Not Increased Replication, Tissue Tropism, or Virulence in Chickens

Abstract: bWe constructed a reverse genetics system for avian paramyxovirus serotype 7 (APMV-7) to investigate the role of the fusion F glycoprotein in tissue tropism and virulence. The AMPV-7 F protein has a single basic residue arginine (R) at position ؊1 in the F cleavage site sequence and also is unusual in having alanine at position ؉2 (LPSSR2FA) (underlining indicates the basic amino acids at the F protein cleavage site, and the arrow indicates the site of cleavage.). APMV-7 does not form syncytia or plaques in ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 37 publications
4
23
0
Order By: Relevance
“…The cells was fixed with methanol and stained with 1% crystal violet. NDV titers in 50%-tissue-culture-infectious-dose (TCID50) units were determined as previously described [19]. Briefly, confluent DF1 cell monolayers were infected with 10-fold dilutions of virus as described for the plaque assay and incubated in medium without methylcellulose.…”
Section: Methodsmentioning
confidence: 99%
“…The cells was fixed with methanol and stained with 1% crystal violet. NDV titers in 50%-tissue-culture-infectious-dose (TCID50) units were determined as previously described [19]. Briefly, confluent DF1 cell monolayers were infected with 10-fold dilutions of virus as described for the plaque assay and incubated in medium without methylcellulose.…”
Section: Methodsmentioning
confidence: 99%
“…The viruses included biologically-and recombinantly-derived wt viruses as well as several recombinant viruses in which the F protein cleavage site had been modified to be multi-basic and to contain the optimal furin protease cleavage site motif RX(R/K)RQ (signature R and K residues underlined). This was done because the presence of a furin motif in the F protein cleavage site typically facilitates cleavage and is a major determinant of virulence for NDV strains [45,46], although this paradigm is uncertain for the other APMV serotypes [16,18,19]. The present study showed that, except for APMV-5, all of the APMVs under evaluation replicated at varying levels in rhesus macaques without inducing any apparent clinical disease signs.…”
Section: Introductionmentioning
confidence: 68%
“…(ii) a recombinant derivative of wt APMV-2, called rAPMV-2 (type 1 Africa), in which the natural cleavage site was replaced by the cleavage site RRRRRQF that is present in a APMV type 1 strain isolated in Africa [16]; (iii) biologically-derived wt APMV-3 strain parakeet/Netherland/449/75 [9]; (iv) recombinant wt APMV-4 strain duck/Hong Kong/D3/75 [10]; (v) a derivative of rAPMV-4, called rAPMV-4/Fc-BC, in which its natural cleavage site was replaced by the cleavage site RRQKRQF that is present in mesogenic NDV strain Baudette C [19]; (vi) biologically-derived wt APMV-5 strain budgerigar/Kunitachi/74 [11]; (vii) biologically-derived wt APMV-7 strain dove/Tennessee/4/75 [13]; (viii) a recombinant derivative of wt APMV-7, called rAPMV-7/Fcs-5B in which its natural cleavage site was replaced by the cleavage site RRKKRQFI present in a velogenic NDV strain Nigeria/95, and which includes an amino acid substitution in the +2 position relative to the cleavage site [18]; and (ix) biologically-derived wt APMV-9 strain duck/New York/22/78 [15]. All the APMV serotypes except serotype 5 were grown in the allantoic cavity of 9day-old specific-pathogen-free (SPF) embryonated chicken eggs.…”
Section: Cells and Virusesmentioning
confidence: 99%
See 2 more Smart Citations